Unemployment in history - Garraty, John A. 1920-2007.; Burke, Joan Martin ([New York] : Encyclopedia Americana/CBS News Audio Resource Library, 1978)
Discusses unemployment in past and contemporary times, as well as the economic and social problems caused by inflation.
Distributed by Grolier Education Corp., New York.
With: A new look at diabetes / Maria New -- An airborne commander, in war & peace / James Gavin.
Interviewer, Joan Martin Burke.
Recorded Aug. 17, 1978, in New York.
Preservation master.
Shakib
Keywords: Unemployed; Inflation (Finance)